Pain Relief and Post-Operative Outcome in Patients Receiving Tramadol via Thoracic Epidural versus Intravenous Method in Coronary Artery Bypass Graft Surgery - Jigisha Mehta; Dr. Mrugank Bhavsar; Sara Mary Thomas; Pooja Shah; Dinesh Chauhan (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background & Objectives:Acute pain is common after cardiac surgery and can keep patients fromparticipating in activities that prevent postoperative complications especially respiratory complications.Accurate assessment and understanding of pain are vital for providing satisfactory pain control andoptimizing recovery.Our aim of the study was to compare pain relief and post-operative outcome in patients receiving Tramadolvia Thoracic epidural versus intravenous method in coronary artery bypass graft surgery.Methodology: Sixty patients aging 40-65 years posted for off pump coronary artery bypass graft surgerywere selected. They were randomly assigned into two groups.Group IVA (n = 30) received Inj. Tramadol(1 mg/kgiv)and Group TEA (n = 30) received Tramadol 0.5 mg/kgepidurallyhalf an hour before shiftingin cardiac recovery room. Hemodynamic parameters like Heart rate, systolic and diastolic blood pressure,pulmonary artery pressure were recorder for 72 hours postoperatively. We have compared extubation timein both the groups. Pain was assessed by visual analogue scale (VAS). Any patients with the VAS more than4 were treated with rescue analgesic. Duration of analgesia and total no. of rescue analgesia were recorded.Duration of stay in cardiac recovery room and in hospital was also recorded.Observation & Results: We have observed statistically significant difference in hemodynamic parametersbetween two groups with better stability in TEA group from shifting till next 72 hours. Extubation time wasalso earlier in TEA group. Mean duration of analgesia and VAS score was also better TEA group. All theseled to shorter length of cardiac recovery stay and earlier discharge from the hospital with less complication.Conclusion: Thoracic epidural analgesia is better than intravenous technique in terms of earlyextubation,maintaining hemodynamic stability and better postoperative analgesia with reduced length ofcardiac recovery and hospital stay.